Students’ attitudes toward flipped classroom model: Focusing on Iranian advanced EFL learners - Ehsan Namaziandost; Meisam Ziafar; Leila Neisi (Universitas Islam Malang, 2020)
Flipped classroom is an engaging, student-centered approach that has been built to enhance the quality of the classroom time. Generally speaking, this approach, whose implementations are performed mostly in physical sciences, has also recently attracted the attention of educators and scholars in various disciplines. Flipped classroom technology is an advancement that helps learners to enhance engagement, increase motivation and develop their communicative abilities. The current study aimed to examine Iranian advanced EFL learners’ attitudes toward using flipped classroom model. To fulfil this objective, 80 advanced EFL learners answered an attitude questionnaire after 10 sessions instructed in a flipped classroom. After collection the data and analyzing them, the results indicated that the learners’ attitude toward using flipped classroom was significantly positive. Eventually, the researchers concluded with some suggestions for educators to adopt the flipped classroom technology to create better learning environments for their students and to reach better learning consequences.